Outcomes of hepaticojejunostomy for post-cholecystectomy bile duct injury. Issue 3 (March 2023) - Ahmad, Humaid; Zia, Haseeb Haider; Salih, Mohammad; Naseer, Muhammad; Khan, Nusrat Yar; Bhatti, Abu Bakar Hafeez
Objectives: Long-term results of hepaticojejunostomy (HJ) for complex bile duct injury (BDI) remain under-reported. The objective of this study was to assess short-term and long-term outcomes of HJ for post-cholecystectomy BDI. Methods: This was a retrospective cohort study and included patients who underwent Roux-en-Y HJ for BDI (n = 87). Short-term (90-day) and long-term morbidity and mortality were assessed. Results: At presentation, 42 (48.2%) patients had E3 or E4 BDI, 27 (31%) patients had vascular injury, and liver resection was performed in 12 (13.7%) patients. The 90-day morbidity was 51.7% (n = 45), and the 90-day mortality was 2.3% (n = 2). The long-term mortality was 3.4% (n = 3). The 10-year estimated stricture-free survival was 95%. The 10-year estimated overall survival rate was 100% in patients who underwent major hepatectomy and 91% in patients who did not. The 10-year estimated overall survival rate was 100% in patients with vasculobiliary injury and was not reached in patients without vascular injury. Conclusions: Vascular injury with proximal BDI is not uncommon. Excellent long-term outcomes might be achieved with Roux-en-Y HJ for BDI with vascular injury and in patients requiring liver resection.